Board Gender Diversity and Stock Liquidity - Setiawan, Rahmat; Shafiyah Azzahrah, Annisa’ush; Rahmawati, Setia Dwi Ratna (El-Barka, 2023)
This study aims to examine the impact of gender diversity on the board of commissioners and the board of directors on stock liquidity in manufacturing companies listed on the Indonesia Stock Exchange. The research employs a multiple linear regression model. Data were obtained from the companies' financial statements published between 2014 and 2016, as well as from stock trading publications on Yahoo Finance. The independent variables used are gender diversity on the board of commissioners, measured by the ratio of female members on the board of commissioners, and gender diversity on the board of directors, measured by the ratio of female members on the board of directors. The dependent variable in this study is stock liquidity, measured using the Illiquidity Ratio. The results of the study indicate that both gender diversity on the board of commissioners and the board of directors has a significant positive effect on stock liquidity.